Acute effects of jumping and sprinting on hammer throwing performance - Karampatsos, G.; Terzis, G.; Polychronou, C.; Georgiadis, G. (Journal of Physical Education and Sport, 2013)
Purpose: The purpose of the present study was to investigate the acute effect of counter movement jumping (CMJ) or sprinting on hammer throwing performance in experienced hammer throwers. Methods: Six well-trained hammer throwers with best performance 61-74m, participated in the study. After standard warm-up they performed three hammer throwing attempts with maximum effort, separated with 1.5- min interval. Three minutes later, they performed three maximal consecutive CMJs. Immediately after the CMJs, they performed three hammer throwing attempts with maximum effort, separated with 1.5-min interval. One week later, they carried out an identical protocol but they performed a bout of 20m sprinting instead of the CMJs, in order to potentiate shot put performance (interventions were counterbalanced). Muscular strength (1RM in squat, snatch, clean and jerk) was also measured. Results: Hammer throwing performance was significantly increased after CMJs (62.92±4.43m vs. 64.42±5.13m, p=0.047) as well as after 20m sprinting (64.87±3.90m vs. 65.30±4.02m, p=0.013), although the increase in performance was not different between the two interventions (p=0.214). Conclusions: These results suggest that performing 3 CMJs or one bout of 20m sprint with maximum effort just before hammer throwing may be a useful method for acute increases in performance in experienced hammer throwers.